Case Report: Implantation of Dedifferentiated to Poorly Differentiated Thyroid Carcinoma After Endoscopic Thyroid Surgery - Hu, Jin; Xu, Xia; Wang, Shuntao; Dong, Fang; Zhang, Ximeng; Ming, Jie; Huang, Tao (Frontiers in Oncology, 2022)
Background: Endoscopic thyroidectomy is widely accepted for its advantages. However, implant metastasis remains a significant complication of endoscopic thyroidectomy. Methods: This is the first report of breast implantation diagnosed with poorly differentiated thyroid carcinoma following endoscopic thyroidectomy. Results: We present a case of a 35-year-old woman who initially diagnosed with a 3.0 cm conventional papillary thyroid carcinoma after endoscopic thyroidectomy via total areola. Two years later, she was reported with recurring poorly differentiated thyroid carcinoma in the right areola. Implantation after endoscopic thyroidectomy is rare and even rarer is dedifferentiated papillary thyroid carcinoma around the implant site. Conclusions: Stringently evaluated endoscopic surgery indication, appropriate preoperative evaluation, meticulous surgical technique, and adequate protective measures can significantly reduce the incidence of local implantation or recurrence.